2017
DOI: 10.1111/njb.01325
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐physiological potential of jack pine (Pinus banksiana) for assisted northward migration: interactions among photoperiod, [CO2] and moisture stress

Abstract: Climate change will cause northward shifts of climate envelopes for boreal plants, however, the different photoperiod and soil moisture regimes at higher latitudes will likely influence the success of species migrations (natural and assisted). The objective of this study was to assess the effects of photoperiod regime and its interactions with soil moisture and carbon dioxide concentration ([CO 2 ]) on the morpho-physiological processes in jack pine Pinus banksiana. One-year old seedlings were exposed to two [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Dang-supervisor of Marfo, initiated the research, advised Marfo in the entire process of the research, adapted this manuscript from Marfo's dissertation, re-wrote substantial amount of the text, revised figures, and made some new figures Du: contributed to the development of the manuscript Newaz: re-analyzed some of the results, updated the literature and some part of the introduction and discussions photosynthesis (Dang et al 2020), at least in the short term. However, the responses and interactions may be modified by other environmental factors such as nutrient availability (Danyagri and Dang 2013, Li et al 2013, Li et al 2015, Danyagri and Dang, 2014a, b, c, Newaz et al 2016, Newaz et al 2017, Tedla et al 2020); e.g., low nutrient supply reduces the stimulation of photosynthesis by elevated CO 2 (Zhang et al 2006;Cao et al 2007;Ambebe et al 2010;Danyagri and Dang 2014b).…”
Section: As Well As Whole Treementioning
confidence: 99%
“…Dang-supervisor of Marfo, initiated the research, advised Marfo in the entire process of the research, adapted this manuscript from Marfo's dissertation, re-wrote substantial amount of the text, revised figures, and made some new figures Du: contributed to the development of the manuscript Newaz: re-analyzed some of the results, updated the literature and some part of the introduction and discussions photosynthesis (Dang et al 2020), at least in the short term. However, the responses and interactions may be modified by other environmental factors such as nutrient availability (Danyagri and Dang 2013, Li et al 2013, Li et al 2015, Danyagri and Dang, 2014a, b, c, Newaz et al 2016, Newaz et al 2017, Tedla et al 2020); e.g., low nutrient supply reduces the stimulation of photosynthesis by elevated CO 2 (Zhang et al 2006;Cao et al 2007;Ambebe et al 2010;Danyagri and Dang 2014b).…”
Section: As Well As Whole Treementioning
confidence: 99%
“…Gustafson et al (2023) showed that under slight changes in climate, assisted migration may indeed increase biomass production through longer growing seasons and CO 2 fertilization. However, they also showed that under more severe climatic scenarios, assisted migration strategies fail to mitigate the deleterious effects of moisture stress and increase respiration to the detriment of productivity (Newaz et al 2017). They concluded that assisted migration was increasingly unable to maintain ecosystem goods and services with the increasing severity of climate change.…”
Section: Introductionmentioning
confidence: 99%